Republic of Armenia : 2012 Article IV Consultation and Fifth Reviews Under the Extended Fund Facility and Under the Extended Credit Facility, and Request for Waiver and Modification of Performance Criterion-Staff Report; Press Release; Public Information Notice; and Statement by the Executive Director for Republic of Armenia. (IMF Staff Country Reports; Country Report, 2013)
The postcrisis recovery in Armenia has accelerated, but challenges remain. Economic policies have been broadly consistent with IMF advice. Credit growth has been strong, especially in foreign currency (FX). The banking system is sound. The central bank (CBA) is improving the regulatory and supervisory framework in line with Financial Sector Assessment Program (FSAP) recommendations. Risks are mainly on the downside and come from potential external shocks, political uncertainties, and regional conflicts. Strong adjustment is continuing in 2012 with the deficit again expected to be lower than budgeted.